(+5)+(+25)=
(+5)+(-25)=
(-5)+(+25)=
(-5)+(-25)=
5-(-25)=
a) (-25)*(+5)= b)(-25):(-5)=
a) (+25)*(-5)= b)(-25):(+5)=
Răspunsuri la întrebare
Răspuns de
2
(+5)+(+25)= 5+25=30
(+5)+(-25)=5-25=-(25-5)=-20
(-5)+(+25)=-5+25=+(25-5)=20
(-5)+(-25)=-5-25=-(5+25)=-30
5-(-25)=5+25=30
(-25)×(+5)=-(25×5)=- 125
(+25)×(-5)=-(25×5)=-125
(-25):(-5)=+(25:5)=5
(-25):(+5)=-(25:5)=-5
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
9 ani în urmă
Istorie,
9 ani în urmă